Monte Carlo simulation of activity measurements by means of 4pb-g coincidence system - Takeda,Mauro N. (2004)
The methodology for simulating all detection processes in a 4pb-g coincidence system by means of the Monte Carlo technique is described. The goal is to predict the behavior of the observed activity as a function of the 4pb detector efficiency. In this approach, the information contained in the decay scheme is used for determining the contribution of all radiations emitted by the selected radionuclide, to the measured spectra by each detector. This simulation yields the shape of the coincidence spectrum, allowing the choice of suitable gamma-ray windows for which the activity can be obtained with maximum accuracy. The simulation can predict a detailed description of the extrapolation curve, mainly in the region where the 4pb detector efficiency approaches 100%, which is experimentally unreachable due to self absorption of low energy electrons in the radioactive source substrate. The theoretical work is being developed with MCNP Monte Carlo code, applied to a gas-flow proportional counter of 4pi geometry, coupled to a pair of NaI(Tl) crystals. The calculated efficiencies are compared to experimental results. The extrapolation curve can be obtained by means of another Monte Carlo algorithm, being developed in the present work, to take into account fundamental characteristics of a complex decay scheme, including different types of radiation and transitions. The present paper shows preliminary calculated values obtained by the simulation and compared to predicted analytical values for a simple decay scheme.